Osteoradionecrosis of the Hip, a Troublesome Complication of Radiation Therapy: Case Series and Systematic Review - Xu, Sheng-hao; Tang, Jin-shuo; Shen, Xian-yue; Niu, Zhi-xin; Xiao, Jian-lin (Frontiers in Medicine, 2022)
Background: Osteoradionecrosis of the hip is a serious complication of radiotherapy that is easily overlooked by physicians and patients in the early stages. There are relatively few reports on this subject, so there is no clear scientific consensus for the pathogenesis, early diagnosis, and clinical treatment of hip osteoradionecrosis. In this paper, we report two cases of hip osteoradionecrosis and systematically review the related literature. Case Presentation: We report two cases of hip osteoradionecrosis. One patient successfully underwent total hip arthroplasty in our hospital and recovered well postoperatively. Another patient although we offered a variety of surgical options for this patient, the patient was worried that bone loss would lead to poor prosthesis fixation, resulting in prosthesis loosening and infection, and therefore ultimately refused surgical treatment. Conclusions: With the development of radiological techniques, the incidence of hip osteoradionecrosis is decreasing year by year, but early diagnosis and rational treatment remain challenging. The effects of non-surgical treatment are limited. Early prevention, early detection, and early intervention are crucial to delay or prevent the emergence of more serious complications.